Hydrate-melt electrolyte design for aqueous aluminium-bromine batteries with enhanced energy-power merits - Xingyuan Chu; Jingwei Du; Jiaxu Zhang; Xiaodong Li; Xiaohui Liu; Yongkang Wang; Johannes Hunger; Ahiud Morag; Jinxin Liu; Quanquan Guo; Dongqi Li; Yu Han; et al. (Nature Communications)
Abstract Aluminium-based aqueous batteries hold promises for next-generation sustainable and large-scale energy storage due to the favorable metrics of Al and water-based electrolytes. However, the performance of current aluminium-based aqueous batteries falls significantly below theoretical expectations, with a critical bottleneck of realizing cathodes with high areal capacities. Herein, we present a hydrate-melt electrolyte design utilizing cost-effective AlCl3 and organic halide salts, which enables the demonstration of aqueous Al-Br batteries with enhanced energy-power characteristics. The optimal electrolyte features suppressed water activity and loosely bound halogen anions, attributed to its unique electrolyte structure, where the majority of water molecules engage in robust ion solvation (>98% as suggested by simulations) and halogen anions reside in the outer solvation sheath of cations. These distinctive features ensure good compatibility of the electrolyte with the reversible Br−/Br0/Br+ conversion, enabling cathodes with a high areal capacity of 5 mAh cm−2. Besides, the electrolyte allows for Zn-Al alloying/de-alloying with minimal polarization (around 100 mV at 5 mA cm−2) and a smooth alloy surface. The assembled Al-Br cell delivers an energy density (267 Wh L−1, based on the volume of anode, cathode and separator) comparable to commercial Li-ion batteries and a substantial power density (1069 W L−1) approaching electrochemical capacitors.